Higher Order Thinking Skills (HOTS) Analysis on Teachers’s Questions in the Final Examination of Bahasa dan Sastra Indonesia at Senior High School 7 Medan - Syamsul Arif (BIRCU, 2019)
Higher order thinking skills is important to apply in learning, particularly in making questions tested to studernts. Higher order thinking skills is a cognitive process which encompasses; analysis, evaluation, and create. In accordance with the 2013 curriculum, the questions made for the high school level must achieve the stage of create of the cognitive process. This research found that the teachers’questions did not include evaluation and create of the cognitive process.